EPCO-22. INHERITED POLYMORPHISM IN CHROMOSOME 8Q24 COOPERATES WITH MUTANT IDH1, Trp53 AND ATRX LOSS TO INDUCE LOW-GRADE GLIOMA. (12th November 2021) - Yanchus, Connor; Drucker, Kristen; Kollmeyer, Thomas; Abyzov, Alexej; Lachance, Daniel; Eckel-Passow, Jeanette; Mak, Tak; Taylor, Michael; Zadeh, Gelareh; Dirks, Peter; Jenkins, Robert; Schramek, Daniel
Abstract: Establishing causal links between genetic polymorphisms and increased heritable risk of developing brain cancer is a major challenge. The non-coding single nucleotide polymorphism rs55705857 (A >G) is associated with a ~6-fold increased risk to develop IDH -mutant low-grade glioma (LGG). The rs55705857 G allele has a minor allele frequency of only ~5% in the general population but is found in ~40% of patients with IDH -mutant LGG and patients carrying risk-alleles are diagnosed on average 7-12 years earlier than those carrying non-risk A alleles. This makes rs55705857 one of the highest reported genetic associations with cancer, comparable with inherited BRCA1 gene mutations and the risk of developing breast cancer or other familial glioma genes such as NF1/2, CDKN2A or p53. To generate a LGG mouse model, we combined clonal activation of IDH1 R132H with mutations of Trp53 and Atrx, which resulted in the development of LGG-like brain tumors in 25% of mice. Mutating the highly conserved, orthologous mouse rs55705857 locus to mimic the human risk allele dramatically accelerated tumor development from 463 to 172 days and increased penetrance to 75%. The resulting tumors exhibit elevated R-2-hydroxyglutarate levels, well-differentiated fibrillary neoplastic histology and metabolic rewiring, recapitulating histopathological and molecular hallmarks of human LGG. Mechanistically, we show that the rs55705857 locus resides within a brain-specific enhancer, which shows enhanced activity in IDH-mutant tumors. In addition, we found that the risk allele disrupts OCT2/4 binding, allowing increased interaction with the Myc promoter and increased Myc expression. The hyperactive chromatin status combined with the tissue specificity of this enhancer explains the cooperativity between mutant IDH and rs55705857 and why rs55705857 is associated specifically with IDH -mutant glioma, but not other cancers. Overall, we generated new LGG mouse models, which provide insights into the pathophysiology of this deadly disease and shed light into the heritable predisposition to LGG development.